طريقة ترجمة الكتب العربية إلى الإنجليزية و الإندونيسية بمعهد فونجاء دار السلام الإسلامي فوتوءان دايا باميكاسن - Noer Fadila; Umar Bukhory (IAIN MADURA, 2018)
There is a translation program of Arabic books into English and Indonesian with different methods applied in Pondok Pesantren Puncak Darussalam. This research is to describe translation methods of Arabic books into English or Indonesian and to analyze similarities and differences between the translation methods in two language centers. This is a descriptive qualitative research. It revealed that there are three methods in the translation of Arabic books. Semantic translation (with guidance) and free translation (without guidance) used in the translation of the Arabic books into English in English center, and word-for-word translation used in the translation of Arabic books into Indonesian at the Arabic center. Meanwhile, the similarities are they used the introductory translation; oral translation, word-for-word translation, and the translation process that is still oriented to the source language. The differences are the translation process at English center is more (used two methods) than in Arabic center (used one method), and the use of semantic translation methods in Arabic center inserted elements of semantics, while the application of word-for-word translation in Arabic center inserted the elements of nahwu. Semantic translation in English center included in the category of understanding, meantime word-for-word translation included in the level of analysis.